2022
DOI: 10.3390/ijerph19020780
|View full text |Cite
|
Sign up to set email alerts
|

Exploring High vs. Low Burnout amongst Public Sector Educators: COVID-19 Antecedents and Profiles

Abstract: The COVID-19 pandemic has had a prolonged impact on many people working in different sectors. This paper focuses on the psychological stress consequences of professionals working in the educational sector in Andalucía (Spain). Using a sample of 340 educators, this empirical paper identifies the antecedents and profiles of those that ended up with burnout vs. those that were able to develop resilience. Results from OLS regressions show that regardless of the origins of stress, the principal determinant of burno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(53 reference statements)
0
3
0
1
Order By: Relevance
“…In Germany [137], teachers and social workers are surveyed following a model derived from the Job Demands-Resources theory to predict effects of strains on burnout, job satisfaction, general state of health, and life satisfaction. While some professionals working in the educational sector are burned out, other develop resilience, and thus it is important to identify antecedents and profiles (e.g., support), as evidenced by another study carried out in Spain [138]. Burnout and job satisfaction are additionally examined in a sample of music therapists in Spain [139]; a higher risk of burnout is associated with working longer hours in a palliative care setting.…”
Section: Special Issue On "Occupational Stress and Health: Psychologi...mentioning
confidence: 99%
“…In Germany [137], teachers and social workers are surveyed following a model derived from the Job Demands-Resources theory to predict effects of strains on burnout, job satisfaction, general state of health, and life satisfaction. While some professionals working in the educational sector are burned out, other develop resilience, and thus it is important to identify antecedents and profiles (e.g., support), as evidenced by another study carried out in Spain [138]. Burnout and job satisfaction are additionally examined in a sample of music therapists in Spain [139]; a higher risk of burnout is associated with working longer hours in a palliative care setting.…”
Section: Special Issue On "Occupational Stress and Health: Psychologi...mentioning
confidence: 99%
“…These findings are consistent with the findings of earlier studies. (Ã-zpolat et al, 2022;Muhammad et al, 2021;Peng et al, 2013;Pérez-Luño et al, 2022) Conducted to identify the significant difference between the level of job burnout among the employees affiliated with government and private organizations. Data analysis suggested that job burnout among government officials is higher than among non-government officials; the result indicates that there is a significant difference among burnout levels of officials regarding the sectors they are working in.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, job insecurity was a high risk in private firms because of this. Government sectors were known to take less work and more wages, so employees could feel like they had a sense of job security in terms of giving the best possible performance to the firms (Pérez-Luño, Díez Piñol, & Dolan, 2022). Burnout is mainly caused by a psychological condition that was generated by the environment, and this could make someone less focused at work and more likely to consider giving up right away.…”
Section: Introductionmentioning
confidence: 99%
“…Igualmente, la falta de competencias en el uso de las nuevas tecnologías de la información y la comunicación, la falta de apoyo social, el au mento en la cantidad de horas dedicadas a las clases online, el conflicto trabajofamilia (Amri et al, 2020) y la percepción de incapacidad para controlar una situación (PérezLuño et al, 2022) actuaron como factores de riesgo significativos para el burnout.…”
Section: Introductionunclassified